Educational program in oral health for caregivers on the oral hygiene of dependent elders - Lago, Jéssica Damares; Fais, Laiza Maria Grassi; Montandon, Andréia Affonso Barretto; Pinelli, Lígia Antunes Pereira (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
AbstractObjective Due increased number of elders living in long-term care institutions, actions designs to improve their oral health are essential. Thus, the aim of this study was to evaluate the impact of an educational program for the caregivers through the assessment of the oral hygiene of institutionalized elders.Material and method The education program consisted in lectures to caregivers about oral health that were performed once a month. The subjects were 40 functionally dependent institutionalized elders and 14 caregivers. Hygiene habits, plaque index, and tongue coating/discoloration of the elders were measured before the educational program (baseline- T0) and after 6 (T1), 12 (T2), 18 (T3) and 24 months (T4). Caregivers answered questions about their knowledge, doubts and implementation of dental care (T0 to T4).Result After analyzing the data (Friedman, Chi-square and Spearman α = 0.05), a gradual improvement in the oral hygiene of the subjects was observed, with an increased frequency of brushing (p=0.0005), a change in the brush type (p=0.0065) and a reduction in the plaque index (p<0.05) and tongue coating (p<0.05). Caregivers showed a marked improvement in their dental care knowledge.Conclusion It was concluded that the educational program for caregivers had a positive impact in the oral health of institutionalized elderly observed by the increased in the effectiveness of oral hygiene parameters such as plaque index and tongue coating, contributing to the knowledge gain in hygiene by caregivers.

ResumoObjetivo Devido ao aumento do número de idosos que vivem em instituições de longa permanência são essenciais projetos de ações para melhorar a saúde bucal. Assim, o objetivo deste estudo foi avaliar o impacto de um programa educacional para os cuidadores de idosos institucionalizados por meio da avaliação da higiene bucal.Material e método O programa de educação consistiu em palestras para cuidadores sobre saúde bucal que foram realizadas uma vez por mês. Foram avaliados 40 idosos institucionalizados dependentes funcionalmente e 14 cuidadores. Os hábitos de higiene, o índice de placa e o revestimento/descoloração da língua dos idosos foram avaliados antes do programa educacional (T0) e após 6 (T1), 12 (T2), 18 (T3) e 24 meses (T4). Os cuidadores responderam perguntas sobre seus conhecimentos, suas dúvidas e sobre a implementação de cuidados bucais (T0 a T4).Resultado Após análise dos dados (Friedman, Qui-quadrado e Spearman, α = 0,05), observou-se melhora gradual na higiene oral dos idosos, com maior freqüência de escovação (p = 0,0005), alteração do tipo de escova (p = 0,0065) e redução do índice de placa (p <0,05) e revestimento da língua (p <0,05). Os cuidadores mostraram uma melhoria acentuada no seu conhecimento sobre saúde bucal.Conclusão Concluiu-se que o programa educacional para cuidadores teve um impacto positivo na saúde bucal dos idosos institucionalizados observado pelo aumento na eficácia dos parâmetros de higiene bucal, como índice de placa e revestimento da língua, contribuindo para o ganho de conhecimento em higiene pelos cuidadores.
Programa educacional em saúde bucal para cuidadores sobre a higiene oral de idosos dependentes
Keywords: Caregivers; dental care for aged; education; homes for the aged; old age assistance; Cuidadores; assistência odontológica para idosos; educação; instituição de longa permanência para idosos; assistência à idosos